Border Crossings: Images of the Pachuco in Mexican Literature - Javier Durán (Studies in 20th & 21st Century Literature, 2001)
This study suggests that an analysis of the image of the pachuco in Mexican literature can provide useful insights about the role and position of subaltern expressions as they become integrated into a larger mapping of cultural production. The paper argues that the pachuco's representation in Mexican culture undergoes a series of transformations that ultimately materialize in a symbolic entity which functions as a buffer mechanism of inclusion and/or exclusion. The pachuco is then a contra modern element that becomes de-territorialized from both Mexican and U.S. culture due to its aesthetic and linguistic hybridity which becomes a menace for essentialist and monolithic visions of the nation. Thus, the image of the pachuco is sees as a transnational and translational figure that develops into a two-sided cultural marker in the writings of Octavio Paz and José Revueltas, promoters of Mexico's post-revolutionary cultural project; while in the writings of Carlos Monsiváis the image of the pachuco becomes an indicator of the relationship between the centralized forces that dictate what is to be Mexican and its chaotic periphery, specifically the northern border with the U.S.
Keywords: border narrative; U.S.-Mexican border; border crossing; pachuco; Mexican literature; subaltern expressions; cluture; symbolism; inclusion; exclusion; territory; U.S. culture; Mexican culture; Octavio Paz; transnationality; cultural markers; José Revueltas; carlos Monsiváis; northern border; north